Contemporary musicology and the study of musical practices in Slovenia - Barbo, Matjaž (Muzikološki zbornik, 2020)
Musicology in Slovenia is gradually evolving from a historiographical discipline into a system of intersecting research in the fields of reception history, institutional history, structural and genre analysis, acoustics, critical reflection, semiological analysis, hermeneutical reflection and epistemology. The discontinuities and inhomogeneities we perceive today can even be understood as one of the modes of contemporary musicology.
Keywords: contemporary musicology; methodology; metodologija; musicology; muzikologija; Slovene musicology; slovenska muzikologija; sodobna muzikologija